Penerapan Metode Hungarian pada Perusahaan Jasa (Kasus Minimum) - Idris Gautama So; Haryadi Sarjono; Robertus Tang Herman (Binus Business Review, 2013)
The study aims to find the total of minimum day that must be spent by CV Buah Segar*) in Purwokerto. CV Buah Segar is a company engaged in the field of fresh fruit agribusiness. In solving marketing problems, the company has seven persons who are the most reliable of the 28 employees to be sent to the seven cities of marketing. The company calculates the total of minimum day they could solve the marketing problems in seven cities which have decreased dramatically in total sales. This decrease will affect the expenditure of the company to incur. The results of the seven employees, whom were Joni, Dodi, Tomi, Andi, Iwan, Wibowo, Kuncoro, and Wahyu after assignment minimization method, required 119 days to 7 employees. So that, the average was 17 days for one employee.